Impact of a Soil Cyanobacteria Consortium-Based Bioinoculant on Tomato Growth, Yield, and Fruit Quality - Zineb Hakkoum; Farah Minaoui; Zakaria Tazart; Amer Chabili; Mountasser Douma; Khadija Mouhri; Mohammed Loudiki (Plants)
Cyanobacteria-based bioinoculants represent a sustainable solution for enhancing soil fertility and crop productivity. This research assessed the biofertilizing potential of two indigenous nitrogen-fixing cyanobacteria strains (Nostoc punctiforme Har. and Anabaena cylindrica Lemmerm.) on tomato growth and yield. A greenhouse experiment was conducted to study their effects on soil properties, plant growth and physiology, and fruit yield/quality. The strains were applied individually, as a consortium, or combined with organic or mineral fertilizers at half the standard dose (50%). All bioinoculants improved soil fertility, plant growth, and fruit yield/quality compared to the control. The most significant improvement was observed in the consortium amended with 50% of conventional fertilizer (compost or NPK), compared with individual strains. Correlation analysis revealed strong positive associations between photosynthetic pigments, plant productivity, and fruit biochemical traits, indicating coordinated physiological responses under the applied treatments. The results demonstrated that the consortium of diazotrophic terrestrial cyanobacteria possesses tomato biofertilizer properties that can be efficiently used in crop production. These findings suggest that such formulations offer a cost-effective approach to tomato cultivation and present a sustainable alternative for integrated and optimized fertilizer management.